Os profissionais de saúde diante da violência :mapeando o processo de implantaçãoda notificação na rede básica de saúde em Natal/RN - Galvão, Vanessa Almira Brito de Medeiros (2008)
Violence is a complex and multifarious phenomenon that has convoked the government to think about strategies to face the question. This work is about one of these strategies proposed by brazilian Health Minister: the Individual notification/investigation Card - Domestic Violence, Sexual and/or others Interpersonal Violences . This instrument is a notification protocol which is been implanted in all of the country. This process is in course in Natal/RN. This work is a report of one research realized in five units of basic health care network of Natal/RN concerning this process about the implementation of the violence notification card. The study aims to cartography all the process of card implantation, discussing the used strategies, the drawn course, difficulties and possibilities as well as how the researcher intended to map subjective process involved at health professional acting at violence case and the propose to use the card. Meetings were held at each unit and a daily fieldwork report was used as research instrument. In this investigation it was observed that notifying violence involves a complexity that is not present in other kinds of notification as consequence of the phenomenon characteristic and health workers are invited to act in different perspective that knowledge and instruments of traditional health fieldwork available does not work. It was observed that the notification card, as a possible instrument of intervention, are considered important detectors from process of work at health basic care and health policies. Depending the way the instrument is used, it may incentive different discussions and manners to offer health care or in other way it can reproduce control and vigilance logics. Consequently it is necessary to consider some factors pointed out at this experience, implanting instruments like this, thinking about these limits and possibilities